Gaining User Trust in Crowdsourcing Startup Using Desirability Business Model (Case Study at PT. Gojek in Surabaya) - Wardhanie, Ayouvi; Wulandari, Sri Hariani Eko (Lembaga Penelitian dan Pemberdayaan Masyarakat (LITPAM), 2021)
This study aims to explore the strategy of gaining user trust in a crowdsourcing startup based on the Desirability Business Model. This study may uncover the user trust of crowdsourcing startup which may help startup enhancing engagement and participation from crowd. The difficulties in crowdsourcing is engage user to stay with application for a long time, so this study try to help startup finding indicators to gain user trust. This paper first propose a model to depict the effect of four parameter of Desirability Business Model with User Trust, which may influence Gojek users, then using Stratified Random Sampling Technique with a total sample of 97 people which are the subject is the society in Surabaya that in a month is at least 2 times and a maximum of more than 10 times using the Go Ride application on the Gojek company. The data collection used a questionnaire distributed through google form and social media such as Line and WhatsApp, while for the tabulation stage, it will be processed using Smart PLS-SEM. The results of this study show that of the four indicators in the Desirability Business Model variable only two indicators have a positive effect on user trust firstly, Value Proposition consisting of Performance, Design, Accessibility, Convenience, Risk Reduction, Cost Reduction and Newness then secondly, Channels consisting of Awareness, Evaluation, Purchase and After Sales. To gain user trust on the crowdsourcing startup, business owners can focus on two things firstly, provide beneficial value of the product or service offered to the user and secondly, design channel which can make business communicates with its users to convey a value proposition.